Cryotherapy-Based Interventions to Enhance Recovery After Total Knee Arthroplasty: A Systematic Review - Fayza Eka Zhafirah; Nadia Meilanda Intriani; Sekar Arum Firdausi; Herdina Mariyanti; Adelvia Nabunome; Agun Arya Wijaya (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: Cryotherapy is used as a non-pharmacological adjunctive intervention to support recovery after total knee arthroplasty (TKA). It helps reduce postoperative pain, edema, inflammation, and limited knee movement, which commonly occur during the early recovery phase. Optimal postoperative symptom management is important to support early mobilization, improve functional recovery, reduce analgesic or opioid use, and increase patient satisfaction. Methods: A systematic review of quantitative studies published from 2021 to 2026 was conducted across six databases: PubMed, Scopus, Web of Science, SAGE Journals, ProQuest, and ScienceDirect. Study selection followed PRISMA guidelines, eligibility criteria were structured using the PICOS framework, and methodological quality was assessed using Joanna Briggs Institute (JBI) critical appraisal tools. Results: Twelve studies met the inclusion criteria. The interventions included ice packs, compressive cold therapy, computer-assisted cooling, motorized cold-compression, preoperative hypothermia, and cryoneurolysis. Most studies showed that cryotherapy reduced postoperative pain and swelling, improved knee range of motion, and supported early functional recovery. Several studies also reported reduced opioid consumption, blood loss, and length of hospital stay. Conclusion: Cryotherapy is a promising adjunctive intervention to enhance recovery after TKA, especially when delivered through structured nurse-led protocols. Further studies with standardized protocols and longer follow-up are needed. Keywords: Cryotherapy, Total Knee Arthroplasty, Postoperative Pain, Edema, Functional Recovery, Nursing Intervention.